Funding Michigan K-12 Adequacy Without Rewarding Inefficiency - James J. Walters (Educational Considerations, 2008)
Taxpayers and politicians expect public schools to exercise stewardship and wisdom regarding the use of resources entrusted to them. These public expectations approximate what economists refer to as technical efficiency.
Keywords: research; analysis; data; funding; Michigan